-5p+24=-8(b-6)+6b

Simple and best practice solution for -5p+24=-8(b-6)+6b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5p+24=-8(b-6)+6b equation:


Simplifying
-5p + 24 = -8(b + -6) + 6b

Reorder the terms:
24 + -5p = -8(b + -6) + 6b

Reorder the terms:
24 + -5p = -8(-6 + b) + 6b
24 + -5p = (-6 * -8 + b * -8) + 6b
24 + -5p = (48 + -8b) + 6b

Combine like terms: -8b + 6b = -2b
24 + -5p = 48 + -2b

Solving
24 + -5p = 48 + -2b

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + -5p = 48 + -24 + -2b

Combine like terms: 24 + -24 = 0
0 + -5p = 48 + -24 + -2b
-5p = 48 + -24 + -2b

Combine like terms: 48 + -24 = 24
-5p = 24 + -2b

Divide each side by '-5'.
p = -4.8 + 0.4b

Simplifying
p = -4.8 + 0.4b

See similar equations:

| 2/3-q=q | | 3/2-q=q | | 8(x+4)=2(x+34) | | 2+5n=4n-20 | | m-(-2)=3 | | 2(x-3)=66-6x | | 6-3n=5n+22 | | 142-4x=6-10x | | 7(2x-1)=-4(6-2x) | | X(25+10)=45 | | 90+0.3m=70+.5m | | 2x=3(1-x)-(x+1) | | -6=5+e | | -2(y-3)=-3(6-2y) | | 2(z+1)=3(z-4) | | 5m-2m+16=10 | | -7x+49=7 | | 13=3y+9 | | 3m-m=3 | | 11-4p=26-9p | | 7x-12=4x+30 | | 2(8n-10)=9n+8 | | 5.4a-12.7=1.3-1.6a | | -5=13-3M | | 2x^2-20x-78=0 | | -7+3x=-73 | | 10*x-2*5=16 | | -3(+5)=3(x-1) | | -3+4x=-35 | | 5x^6=-320 | | 5m+3=9-4m | | 5x+6=2-3x |

Equations solver categories